2015
DOI: 10.1016/j.jhep.2014.09.026
|View full text |Cite
|
Sign up to set email alerts
|

TRIM24 suppresses development of spontaneous hepatic lipid accumulation and hepatocellular carcinoma in mice

Abstract: Background and Aims Aberrantly high expression of TRIM24 occurs in human cancers, including hepatocellular carcinoma. In contrast, TRIM24 in the mouse is reportedly a liver-specific tumor suppressor. To address this dichotomy and uncover direct regulatory functions of TRIM24 in vivo, we developed a new mouse model that lacks expression of all Trim24 isoforms, as the previous model expresses normal levels of Trim24 lacking only exon 4. Methods To produce germline-deleted Trim24dlE1 mice, deletion of the promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 41 publications
(59 reference statements)
1
54
0
Order By: Relevance
“…Hao2 is strongly induced in E1/E2-KO male liver, but to only ~60% the level of control (wild-type) female liver, and this increase in expression may not be not sufficient to counteract the severe liver injury generated by loss of Ezh1/Ezh2. Furthermore, other female-biased genes that have been recognized as tumor suppressors in HCC, such as Trim24 [71, 72], are not up-regulated in male E1/E2-KO liver. Further studies are needed to determine the extent to which the higher expression of such liver disease-protective genes in female liver contributes to sex-differences in liver fibrosis and liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hao2 is strongly induced in E1/E2-KO male liver, but to only ~60% the level of control (wild-type) female liver, and this increase in expression may not be not sufficient to counteract the severe liver injury generated by loss of Ezh1/Ezh2. Furthermore, other female-biased genes that have been recognized as tumor suppressors in HCC, such as Trim24 [71, 72], are not up-regulated in male E1/E2-KO liver. Further studies are needed to determine the extent to which the higher expression of such liver disease-protective genes in female liver contributes to sex-differences in liver fibrosis and liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…L iv e r (T C Analyses of genomic data of tumors with high levels of MDM4 and p53 mutation or deletion from data sets accessed and prepared using the cBioPortal for Cancer Genetics (www.cbio portal.org) (Cerami et al 2012;Gao et al 2013 (Hakem et al 2011;Migliorini et al 2011;Jiang et al 2015), studies have shown strong evidence of regulation in vitro. The in vivo models to date have modeled loss of these enzymes, not overexpression, which would be expected to better mimic the pathological state for a negative regulator of p53 during tumorigenesis.…”
Section: Cross-cancer Alteration Summary For Mdm4mentioning
confidence: 99%
“…In this study, we focused on TRIM24, a newly identified TRIM family member as a binding partner of dysbindin in our yeast two-hybrid (Y2H) screen. TRIM24 has been studied thus far only in the context of cancer (32)(33)(34). TRIM24 is known to be interacting with tumor protein 53 (p53), leading to its degradation by ubiquitination and hence affecting genomic stability, cell cycle arrest, and apoptosis (35).…”
mentioning
confidence: 99%